Thermally Induced Spin Transition in a 2D Ferrous Nitroprusside. Issue 47 (13th October 2019) - Avila, Yosuan; Plasencia, Yosdel; Osiry, Hernandez; Martínez‐dlCruz, Lorena; González Montiel, Marlene; Reguera, Edilso
Abstract : This study reports the intercalation of pyridine molecules between neighboring layers of two‐dimensional (2D) ferrous nitroprusside. In the material under study, the stacking of neighboring layers results in the formation of a long range ordered solid, where the 3D structure is supported by dipole‐dipole attractive interactions between neighboring pyridine molecules in the interlayer region. No chemical interactions were observed between layers, which preserve their identity as a 2D material. In this hybrid inorganic–organic solid, a thermal induced spin transitions from high to low spin on cooling and then from low to high spin on heating were observed. Such thermal induced spin crossover transition takes place with a pronounced hysteresis of 18 K, according to the magnetic and DSC measurements. That spin crossover transition is characterized by an extremely small structural change, involved a unit cell volume reduction from the high to low spin states of only 0.7 % and a related Fe–NPyridine distance shortening of 0.10 Å. The two spin states and the transition between them were additionally characterized from magnetic and DSC data and, Raman and Mössbauer spectra. Abstract : Thermally induced spin transition (spin crossover) in Fe(pyridine)2 [Fe(CN)5 NO]. This transition involves atypical structural changes, barely 0.7 % of volume reduction from the high to low spin transition, with Fe–NPyr interatomic distance variation of only 0.10 Å. The related enthalpy change is atypically small, in the 5.25–5.30 kJ/mol range. The spin transition is also clearly appreciated in the sample color change and through the corresponding Raman spectra.